Sobrecarga laboral en las enfermeras de la unidad de cuidados intensivos (UCI) en el Hospital General Esmeraldas Sur Delfina Torres de Concha - Luna Tarapues, Suany Nathaly (2019)
The present study was carried out in the General Hospital Esmeraldas Sur Delfina Torres De Concha in the Intensive Care Unit whose objective was to develop educational strategies that contribute to the reduction of work overload in nurses. When developing the investigation, the triggers of the problem were determined, such as: physical, biological, ergonomic and chemical, generating inconvenience not only in the internal user but also in the external user. A descriptive, qualitative, quantitative and field study was carried out, using a survey that identified work overload in nursing staff in the intensive care unit. Evidence of ignorance of teamwork, there are bad interpersonal relationships, generating physical and mental load, affecting professional performance in the different activities of direct patient Care. Given these results, the stated objective was achieved, which contributed to improving interpersonal and labor relations, reducing workload in the UCI